Analisis Pengembangan Budidaya Rumput Laut di Wakatobi: Ekonomi Biru, Resiliensi Penghidupan, dan Pemberdayaan Masyarakat Pesisir - Ode Mansyur, La; Taswin Munier, Muh.; Rumpa, Arham; Nasrun, Nasrun; Ikhsan, Nur; Harudin, Harudin; Hindi, Patta; Robin, Robin (Jurnal Ilmu Manajemen Sosial Humaniora (JIMSH), 2026)
Study findings on seaweed cultivation commonly examine production feasibility, livelihood contributions, or blue economy governance in isolation; consequently, the mechanisms connecting policy support, community participation, technology adoption, economic resilience, and wellbeing in small-island sea-grape systems remain insufficiently explained. This study assesses the feasibility and development mechanisms of seaweed (Caulerpa sp.) cultivation and develops a Policy Participation Technology Resilience Wellbeing Framework (PPTRW) for community based blue economy implementation. A convergent mixed-methods design was employed. Quantitative data were collected through a purposive survey of 150 respondents comprising 56 fishers, 62 seaweed farmers, and 32 marine-tourism actors, while qualitative evidence was obtained from observation, in-depth interviews, and documentation. The analyses included descriptive statistics, the revenue–cost ratio, household-income contribution, Pearson correlation, break-even sensitivity analysis, thematic analysis, TOWS, and data integration using a joint display. The business recorded an R/C ratio of 1.72, an average reported income of IDR 3,150,000 per production cycle, a 22% contribution to household income, and a positive association between business experience and income (r=0.61; p<0.05). Ceteris paribus, the enterprise remains at break-even until revenue falls by approximately 41.86% or costs rise by 72%. Qualitative findings indicate that experience improves site selection, quality control, efficiency, and market access, whereas local institutions, post-harvest technology, and ecotourism integration create pathways toward resilience. The study’s novelty lies in the PPTRW framework, which integrates Blue Economy, Sustainable Livelihoods, and Community Empowerment perspectives at the small island village level. Policy implications include cultivation clusters, marketing cooperatives, cold-chain technology, educational ecotourism packages, and ecological carrying-capacity monitoring.